Multivariate neuroanatomical correlates of behavioral and psychological symptoms in dementia and the moderating role of education - Kwak, Seyul (Neuroimage Clin, 2020)
Neuropsychiatric symptoms are commonly observed as brain pathology progresses with dementia. Behavioral and affective disturbances underly the distinct neuroanatomical basis of typical symptoms of cognitive impairment; however it remains unclear whether enriched intellectual experience, such as educational attainment, can mitigate the effect of brain structural patterns on neuropsychiatric symptom severity. We utilized the Open Access Series of Imaging Studies (OASIS-3) dataset, which includes brain structural MRI and behavioral symptom evaluation. We included 904 older adults who were mostly cognitively normal, clinically diagnosed with very mild to moderate Alzheimer’s disease, or other types of dementia. Canonical correlation analysis was used to identify the patterns of multivariate association between the gray matter structure and neuropsychiatric symptom severity. First, we identified two canonical modes capturing the distinct neuroanatomical basis of common and mood-specific factors of neuropsychiatric symptoms. The first common pattern reflected a smaller volume in the amygdala and adjacent temporal regional thickness. The second mood-specific pattern reflected patterns in lateral and orbital prefrontal regional thickness. In the external correlational analysis, the two canonical correlations reflected global brain volume and white matter lesions; however, the second pattern was not associated with functional impairments or cognitive function. Moreover, older adults with higher education showed an attenuated severity of behavioral symptoms, even with the presence of a brain structural pattern. Our findings suggest that educational attainment, as a proxy of cognitive reserve, can mitigate the severity of behavioral and affective symptoms of dementia.